Tipologi Dakwah Nabi Musa ‘Alaihissalam Perspektif Al-Qur’an (Kajian Tafsir Tematik) - Daulay, Ahmad Rizki; Jamal, Khairunnas; Husin, Nixson (Jurnal An-Nur, 2023)
This research discusses the preaching of Prophet Musa 'Alaihissalam from the typology of his preaching, both with the rulers in his era, his brothers and he mad'u. So this study examines the views of commentators regarding the Typology of Da'wah of Prophet Musa 'Alaihissalam from the Perspective of the Qur'an. This research is a library research and the methodology used in this research is a thematic study. The data related to this study were collected through literature study and presented with descriptive analysis techniques, namely by explaining the relevant verses, referring to the Qur'an and its interpretations as primary data and related literature books as secondary data. The research that the writer will do is thematic research, so to get objective results, the research steps or data collection that the writer will do refers to the Maudhuiy interpretation research method made by Dr. Abd Al Hayy Al Farmawi. The results of this study show that the Prophet Musa preached with the first type, the type that emphasizes faith. The second type, with the theoretical type. a theocracy is a system of government that upholds and is guided by divine principles. The third type, the patient type. The fourth type, puts forward optimism, the fifth type, qualified knowledge. The sixth type, the assertive type. The seventh type, the type of altruism. Keywords: Da'wah, type, Moses